The study of job satisfaction among employees in Petronas company / Rhurdy Hubert - Hubert, Rhurdy (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2009)
This research study on "Job Satisfaction among Employees in Petronas Company" is consist 50 respondents participated in the survey. The research objectives are to know the study the factors associate to the job satisfaction among employees, to know the differential perception between male and female towards job satisfaction and suggest several ways and recommendation to increase job satisfaction. Compensation factor, workplace environment factor and policy factor are the factors or drivers that determine in this research project. With using the associate analysis, the research found that no of the three factors has a correlation to the job satisfaction. Mann-Whitney test also shows that no different perception between male and female towards importantness of job satisfaction. But, the recommendations are given to increase job satisfaction.